Relevansi Tafsir Ayat-Ayat tentang Kehidupan Akhirat terhadap Penguatan Nilai Rukun Iman dalam Pendidikan Islam - Dwi Afriyanto (PT. Nawa Edukasi Nusantara, 2025)
This study explores the relevance of Qur’anic verses on the afterlife—specifically Q.S. Qaf: 19–23, Al-A‘la: 14–17, and Al-Ḥadīd: 20—toward strengthening the values of faith in Islamic education. The study addresses the gap between students' cognitive understanding of eschatological beliefs and their moral application in daily life. Using a qualitative design with thematic exegesis (tafsir maudhū ‘ī) and literature-based analysis, the research highlights how these verses can serve as foundational elements in forming students' spiritual awareness and moral accountability. The findings show that belief in the afterlife is not only theological but plays an ethical and pedagogical role in shaping behavior and educational systems. This includes curriculum orientation, character development, evaluation principles, and administrative practices inspired by the Qur’anic worldview of accountability. The study concludes that eschatological faith should be integrated across disciplines, not limited to religious subjects. It further recommends future research to design practical models of eschatological learning and contextual evaluation instruments for Islamic education.